Sensing signal conditioning circuit design and analysis for emerging pressure sensing technology - Li, Yuanbo (2016)
As the sensing materials develop more and more rapidly, some advanced sensing technologies have emerged in medical applications. These technologies own amounts of advantages so that they have been applied in market popularly. However, there still exist some limitations and challenges to be solved. In this FYP, three emerging sensing technologies are reviewed. They are piezoelectric, capacitive and piezoresistive sensing, respectively. Investigations on principle, advantages, disadvantages, applications and challenges of the three technologies are done. After a comparison of their sensing performance and fabrication cost, capacitive sensing is selected to have an investigation. An OpAmp-based switched-capacitor integrator with a sample and hold circuit is selected to measure the sensor’s capacitance change by converting the capacitance to voltage. In this work the capacitance measurement circuit is built and simulated to model a measurement of human radial artery pulse pressure from 20-75 mmHg. The measurement aims to detect human blood pressure from 40-200 mmHg. In the simulation, the target pulse signal frequency is set to 1Hz and sampling frequency is set to 5KHz. The capacitance measurement circuit is built in 0.18μm CMOS technology. In this study, the Op Amp is an ideal model to verify the circuit function. This simulation confirms that this circuit realizes the function to test human radial artery pulse pressure. In the future, we will investigate the influence on the capacitance measurement circuits by temperature, noise, and parasitic capacitance, and find the circuit level solution to improve resolution, sensitivity and reliability.